If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1253 + -2x = 5x + -1 Reorder the terms: 1253 + -2x = -1 + 5x Solving 1253 + -2x = -1 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 1253 + -2x + -5x = -1 + 5x + -5x Combine like terms: -2x + -5x = -7x 1253 + -7x = -1 + 5x + -5x Combine like terms: 5x + -5x = 0 1253 + -7x = -1 + 0 1253 + -7x = -1 Add '-1253' to each side of the equation. 1253 + -1253 + -7x = -1 + -1253 Combine like terms: 1253 + -1253 = 0 0 + -7x = -1 + -1253 -7x = -1 + -1253 Combine like terms: -1 + -1253 = -1254 -7x = -1254 Divide each side by '-7'. x = 179.1428571 Simplifying x = 179.1428571
| 45(0)-4(12(0)-3)=12 | | 4(3x+1)=12x+19 | | =02x^2-7x-4 | | 56x+67x+20= | | 6p-21=3p-12 | | (x+3)5=9(x-13) | | 7y+4+21=12y | | 4a^2+12a+2=0 | | 67-3x=15x+21 | | 60x^4y^6-15x^2y^4+20xy^3=0 | | 11p^4+56p^3q+5p^2q^2= | | 10x^2-2x-4=0 | | 60x^4y^6-15x^2y^4+20x=0 | | 56=8y+16x | | c^3-512=0 | | 5x^2y+6xy^2+y^3= | | 5x+1+15=7x | | 8t+5=5 | | 7x-9=54 | | =5-2/7 | | 2m^2+8m+4=0 | | 42a^2-33a-45= | | 6x-18=2(x-6) | | 0.6x+3.4=2.5-1.3x | | 12a^2-2a-30= | | 12n^2-n=6 | | n^2-n-42=0 | | x=50 | | 0.4x-2.5=3.8+1.3x | | 30a^2-22a-28= | | 8*90-57= | | 7x-11=5x+x+3 |